Simulation Analysis of Cylindrical Shell Cavity Noise with Melamine Foam Lining - Menghui Qi; Bin Li; Shilin Yan; Qinghua Yan; Qiyu He (Shock and Vibration)
To solve the problem of the harsh midlow frequency noise of rocket fairing, the cylindrical section of the protective precision instrument fairing is simplified as cylindrical shells, and different lining strategies of melamine foam (MF) are studied experimentally and numerically. Based on Virtual.Lab Acoustic software, a finite element model of the cylindrical cavity is established, and the correctness is verified by comparison with the measured data. On that basis, the influences of the lining position of different thickness MF on the noise reduction of cylindrical shells are investigated. It is shown that the thickness and location of the laying material have a significant effect on the noise reduction at the same specific gravity.